The Effect of Adverse Selection and Psychological Capital on Decision Making Involving Escalation Situations: An Experimental Study - I Made Narsa; Niluh Putu Dian Rosalina Handayani Narsa (Jurnal Ilmiah Akuntansi, 2021)
This study examines the determinant of structural variable (adverse selection) and psychological variable (psychological capital – PsyCap) on manager’s tendency to escalate their commitment. This study used 2 x 2 factorial experimental design as a research method. The participant of this study is management and accounting master students who act as the surrogate of project manager. Used ANOVA as the data analysis technique, this study found a main effect of adverse selection and PsyCap in predict the escalation of commitment. However, there is no effect of the interaction between those two variables on escalation of commitment. This study contributes to the literature of escalation of commitment as well as psychological capital literature, considering that PsyCap is always associated with positive outcome but this study found that the high PsyCap might also predict undesirable outcome such as escalation of commitment.